FORECASTING DATA INFLASI YEARS ON YEARS KOTA BATAM TAHUN 2017-2020 - A'rsyil Majiid; Vitri Aprilla Handayani (JURNAL SINTAK, 2023)
Forecasting year-to-year inflation data and minimizing the occurrence of a decrease in CPI/Inflation so that there are no changes in the price index within the specified time. The method used to use forecasting techniques is ARIMA (Autoregressive Integrated Moving Average). ARIMA is also often called the Jenkins time series method. The data used is secondary data obtained from the Central Statistics Agency, namely year-to-year inflation data for 2017-2020. The results obtained from the 10 time series models used in forecasting the infallible value of the city of Batam for 2017-2020 are ARIMA (2,2,1) which has the smallest MS value of 0.05708 so it is used in forecasting, as well as an increase in inflation